Distal Factors Associated With Proximal Overdose Risk Behaviors and Recent Non-Fatal Overdose Among a Sample of People Who Use Illicit Opioids in New York City - Elliott, Luther (Journal of drug issues, 2024)
This analysis identifies factors associated with overdose risk behaviors and non-fatal overdose among a sample of 577 adult-age people who use illicit opioids and live in NYC. Survey data--which included outcome measures assessing (1) past 30-day non-fatal overdose and past 30-day overdose-related risk behaviors and (2) predictors representing potential risk and protective factors—were analyzed using bivariate and Poisson regression techniques. Results indicate being 41–56 years in age, being widowed, using cannabis, injecting, and having greater pain severity and mental health challenges were associated with greater risks. Current employment, homelessness, and prescription of medications for opioid use disorder were associated with fewer risks. Being 57+ was negatively associated with past-month overdose; higher pain severity and opioid related withdrawal were positively related, as were employment, cannabis use, and injection. Findings suggest the importance of expanding access to MOUD and tailoring OD prevention interventions for mental health and pain management services.